ANALYSIS OF FIGURATIVE LANGUAGES IN THE SONGS OF MOVIE “SPIRIT: STALLION OF THE CIMARRON” - Syamsu, Ahmad Riwaldi Yahdian; Weda, Sukardi (Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
This research discusses figurative languages found in the songs of movie “Spirit: Stallion of the Cimarron”. It aims to determine the types of figurative languages in the songs of movie “Spirit: Stallion of the Cimarron” by used theory of figurative language by Abrams (1999) and elaborate the function of each types of figurative languages found based on Perrine’s (1969) theory of the function of figurative language. The research method used in this study is a qualitative descriptive method. The data are taken from lyrics from 11 songs in the movie “Spirit: Stallion of the Cimarron”. The result showed there are five types of figurative language found in songs of the movie “Spirit: Stallion of the Cimarron” which are metaphor (5), simile (3), hyperbole (9), personification (4) and symbol (1). Moreover, the researcher found all functions of figurative language. The first function, to give imaginative pleasure (8) found in lyrics contain simile, hyperbole, personification and symbol. The second function, to bring additional imagery (1) found in lyrics, contains hyperbole. The third function, to increase emotional intensity (10) applied as some lyrics contained metaphor, hyperbole and personification function. Lastly, the function to say much in a brief compass (3) applied as metaphor, simile and hyperbole function. Each of these functions serve as a figurative language’s type function based on its meaning and context.